The interaction of fertilization in nursery and field on survival, growth and the frost heaving of birch and spruce - Hreinn Óskarsson 1971-; Sigríður Júlía Brynleifsdóttir 1974- (2009)
The interaction of nursery fertilization and field fertilization at the time of planting on survival, growth and frost heaving of container seedlings of birch (Betula pubescens) and Sitka spruce (Picea sitchensis) was tested in a factorial trial on four sites in Iceland. A trial with nutrient loading of seedlings was done during a four week period in May-June in a nursery prior to planting. Seedlings were divided into three groups and irrigated twice weekly for four weeks with; control = pure water; Sc1 = 10 g fertilizer m-3 water and Sc2 = 20 g m-3. Field experiments were established on two sites in east Iceland and two in west Iceland. On each site the three nursery treatments were split up by giving the seedlings either a single application of 15 g seedlings-1 of the fertilizer “Gróska II” or no fertilizer. The pre-treatments Sc1 and Sc2 increased the shoot growth significantly during the first summer, and this effect was still seen on the volume growth three years later. The field fertilization at planting had a positive effect on survival and growth and also reduced frost heaving, and the best growth and survival rates were obtained by pre-treatment Sc2 followed by field fertilization. Mikil aukning hefur orðið í skógrækt á síðustu árum á Íslandi með tilkomu landshlutabundinna skógræktarverkefna sem styrkt eru af ríkinu. Miklir hagsmunir felast í því að faglega sé staðið að ræktun, meðferð og gróðursetningu trjáplantna. Í greininni eru kynntar niðurstöður tilraunar þar sem skoðuð voru áhrif mismunandi áburðarstyrks í vökvunarvatni á bakkaplöntur af birki (Betula pubescens) og sitkagreni (Picea sithensis) síðustu fjórar vikurnar fyrir gróðursetningu og einnig áburðargjafar við gróðursetningu í foldu, og áhrif meðferðanna á lifun, vöxt og frostlyftingu. Tilraunin var gerð í gróðrarstöð í maí og voru plöntur vökvaðar tvisvar í viku í fjórar vikur með þrenns konar áburðarvatni, viðmiðun = hreint vatn, Sc1 = 10 g áburður m-3 og Sc2 = 20 g m-3. Voru plönturnar svo gróðursettar í fjóra tilraunareiti, tvo á ...